Are workers motivated by the greater good? - Mirco Tonin (IZA World of Labor, 2015)
Employees show more commitment to an employer that promotes the greater good, and they work harder too. Moreover, many people are willing to give up some of their compensation to contribute to a social cause. Being able to attract a motivated workforce would be particularly important for the public sector, but this goal remains elusive. Indeed, there is evidence for the public sector that paying people more or underlining the career opportunities (as opposed to the social aspects) associated with public sector jobs is instrumental in attracting a more productive workforce, without having a negative impact on intrinsic motivation.
Keywords: D64; H83; J28; J32; J45; 330; corporate philanthropy; employee motivation; public sector; recruitment